1998
DOI: 10.1046/j.1365-2249.1998.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative intracellular cytokine measurement: age-related changes in proinflammatory cytokine production

Abstract: SUMMARYThe proinflammatory cytokines play a central role in mediating cellular and physiological responses, and levels may reflect immune system effectiveness. In this study, the effect of ageing on the inflammatory response was examined using a novel method to detect production of the proinflammatory cytokines, i.e. tumour necrosis factor-alpha (TNF-a), IL-6 and IL-1b. Peripheral blood mononuclear cells (PBMC) obtained from healthy donors of different ages were incubated for 0, 24, 48 and 72 h with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(77 citation statements)
references
References 23 publications
8
61
1
3
Order By: Relevance
“…TNF-α, IL-6 levels [19] and IL-1, TNF-α levels [3,6] have been reported to increase age-dependently as well. Thus, the development and progression of several age-related diseases are associated with chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, IL-6 levels [19] and IL-1, TNF-α levels [3,6] have been reported to increase age-dependently as well. Thus, the development and progression of several age-related diseases are associated with chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to mitigate against these possibilities in the design and analysis of the study with the following measures: the PBMC stimulation period was limited to 3 h to minimize the potential for adaptive, lymphocyte-mediated cytokine expression and for secondary feedback modulation of the response observed. 25 We included LPS as an inflammatory stimulus that it exerts its biological effects through innate TLR signaling pathways. We used titanium particles as the particulate challenge rather than polyethylene as previous studies have shown that both titanium and polyethylene particle stimulate cytokine …”
Section: Immune Response In Osteolysis-susceptible Patientsmentioning
confidence: 99%
“…The data regarding cytokine and chemokine secretion are ambiguous in several studies using human monocytes from aged or young individuals activated in vitro with mitogens or LPS. Although the majority of the studies indicate an increase in the levels of pro-inflammatory factors such as IL-6 and IL-8 (Ershler et al ., 1993;Clark & Peterson, 1994;O'Mahony et al ., 1998;Roubenoff et al ., 1998;Sadeghi et al ., 1999;Hasegawa et al ., 2000;Mariani et al ., 2002), others find decreased levels (Gon et al ., 1996;Beharka et al ., 2001) or no changes at all (Ahluwalia et al ., 2001). Differences in the genetic heterogeneity and health status of the test population, in addition to the experimental and assay conditions, may all contribute to the discrepancy in these results.…”
Section: Cytokine and Chemokine Secretionmentioning
confidence: 99%